Optical skyrmions from metafibers with subwavelength features - Tiantian He; Yuan Meng; Lele Wang; Hongkun Zhong; Nilo Mata-Cervera; Dan Li; Ping Yan; Qiang Liu; Yijie Shen; Qirong Xiao (Nature Communications)
Abstract Optical skyrmions are an emerging class of structured light with sophisticated particle-like topologies with great potential for revolutionizing modern informatics. However, the current generation of optical skyrmions involves complex or bulky systems, hindering the development of practical applications. Here, exploiting the emergent “lab-on-fiber” technology, we demonstrate the design of a metafiber-integrated photonic skyrmion generator. We not only successfully generate high-quality optical skyrmions from metafibers, but also verify their remarkable properties, such as topology switchability and topology stability with subwavelength polarization features beyond the diffraction limits. Our flexible fiber-integrated optical skyrmions platform paves the avenue for future applications of topologically-enhanced remote super-resolution microscopy and robust information transfer.